2023
DOI: 10.3390/land12020401
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Integration of SWAT and Multi-Objective Optimization Algorithms for Evaluating Efficiencies of Agricultural Best Management Practices to Improve Water Quality

Abstract: Nitrate is one of the most complicated forms of nitrogen found in aquatic surface systems, which results in the eutrophication of the water. During the last few decades, due to agriculture and animal husbandry activities, as well as urban development, a significant amount of pollutants have accumulated in the Jajrood river in northern Iran. In this research, we simulated nitrate load in a rural watershed to assess the outlet stream’s qualitative status and evaluate the influence of best management practices (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 114 publications
0
3
0
Order By: Relevance
“…The alarming rate of TN and TP loading entering water bodies has posed critical challenges, notably the escalating issue of eutrophication in lakes, compromising the quality of drinking water and impacting various water-related activities [20][21][22]. In order to minimize the adverse effects of nutrient pollution in water bodies, many researchers in recent studies suggested that conservation methods, also known as Best Management Practices (BMPs), including vegetative filter strips (VFS), grass waterways (GWW), fertilizer reduction (FR), crop rotation (CR), and cover crop (CC) have been widely recommended as viable mitigation measures to reduce non-point pollution and improve water quality in impaired waterbodies [23][24][25]. However, the efficacy of BMPs is case by case and mostly limited to site-specific locations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alarming rate of TN and TP loading entering water bodies has posed critical challenges, notably the escalating issue of eutrophication in lakes, compromising the quality of drinking water and impacting various water-related activities [20][21][22]. In order to minimize the adverse effects of nutrient pollution in water bodies, many researchers in recent studies suggested that conservation methods, also known as Best Management Practices (BMPs), including vegetative filter strips (VFS), grass waterways (GWW), fertilizer reduction (FR), crop rotation (CR), and cover crop (CC) have been widely recommended as viable mitigation measures to reduce non-point pollution and improve water quality in impaired waterbodies [23][24][25]. However, the efficacy of BMPs is case by case and mostly limited to site-specific locations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, several studies reported that VFS could potentially reduce the nutrient level by 31% to 90% [33,34]. Additionally, several investigations have demonstrated that crop rotation can lead to a significant decrease in nutrient load, with reductions ranging from 15% to 32% [7,25,35]. The application of cover crops has been proven to be effective to decrease nitrogen and phosphorus by 20% to 38% [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the choosing an efficient and effective optimization framework in a complex model (e.g., SWAT) is becoming a critical issue to decrease the running model time. For instance, Hashemi Aslani et al (2023) established a connection between the SWAT model and MOPSO as a multi-objective optimization algorithm. Their study aimed to minimize various objective functions, such as the number of best management practices and nitrate concentration, while considering different scenarios.…”
Section: Introductionmentioning
confidence: 99%